An Integrated Facility Management System Supported in Vdc and Lean - Bazán Montalto, Alvaro Daniel (2024)
The operational costs during the maintenance phase can account for 15% to 70% of a facility's total life cycle expenses, depending upon the type and size of the project. This paper explores the integration of Virtual Design and Construction (VDC) and Lean methodologies, offering practical solutions to optimize the maintenance operations of an engineering laboratory. A comprehensive literature review was conducted to identify common challenges in facility management and assess existing methods and technologies to address these issues. This research introduces the concepts of VDC and Lean within maintenance management, proposing an Integrated Facility Management System (IFMS) that applies these frameworks to the operations and maintenance (O&M) processes. The IFMS aims to harmonize the facility's physical structure, organizational dynamics, and procedural workflows, providing a practical roadmap for facility managers and maintenance professionals. Implemented in an engineering laboratory in Lima, Peru, the IFMS has significantly improved maintenance efficiency. The results include a fivefold reduction in the average time required for corrective maintenance and a 50% decrease in the incidence of such maintenance tasks. Finally, applying VDC and Lean principles to the maintenance phase can yield substantial operational benefits, as evidenced by the data from the implemented IFMS.